Development of video games to improve the learning of data structures - Salvador-Ullauri, Luis (2020)
Computer engineering students have little interest in striving to understand the fundamentals of developing data structures at the origins of computing. In order to improve the learning of the Data Structure course, a strategy has been established for students to develop a simple video game in which the implementation of AVL trees, queues, and stacks shows the importance of using data structures during the development of computational applications. This work suggests a method to stimulate the learning of the essential elements of the software through the development of video games to emphasize the importance of the use of Data Structures. The students involved in this practice used graphic tools to represent the insertion and deletion operations that are performed on three types of Data Structures: AVL Tree, queue and stack. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.